Proposing a novel heuristic algorithm for university course timetabling problem with the quality of courses rendered approach; a case study - Tavakoli, Mohammad Mehdi; Shirouyehzad, Hadi; Lotfi, Farhad Hosseinzadeh; Najafi, Sayed Esmaeil (Alexandria engineering journal, 2020)
University course timetabling problem has been and id being considered as an operational issue by researchers. The purpose of University Course Timetabling Problem is to allocate academic courses to the lecturers, time slots and classrooms which must be executed in such a manner to promote to quality of education. In this context, a three-stage heuristic algorithm consisting of lecturers, time slots and classes is proposed. By applying the Days of lecturers’ attendance to total days of planning ratio, Lecturer quality level in planning context, Offering the simultaneous prerequisite and main courses to the all course ratio, Courses presented in the last time-slot to total courses ratio, Surplus classroom capacity to classroom capacity ratio, Full-time lecturer to total lecturers ratio and Number of classrooms assigned to each lecturer to total available classroom ratio indexes, the planning obtained through this newly proposed algorithm is assessed and the response quality is determined. The available data of the subject university’s industrial engineering department is fed in MATLAB software through this algorithm with the objective to have the University Course Timetabling Problem as the output. At its experimental stage, the output is measured through the same indexes revealing that course presentation by the lecturers is 96% of the possible optimum.